Structural seismic design optimization and earthquake engineering : formulations and applications - Plevris, Vagelis, 1976- (Engineering Science Reference, 2012)
"This book focuses on the research around earthquake engineering, in particular, the field of implementation of optimization algorithms in earthquake engineering problems, including simulation issues for the accurate prediction of the seismic response of structures, design optimization procedures, soft computing applications, and other important advancements in seismic analysis and design"--Provided by publisher
"Premier reference source"--Cover
Keywords: Earthquake engineering.; Structural optimization.; elektronické knihy; electronic books